Surgical Challenges in Severe Fixed Extension Deformity of the Right Knee Post Multiple Sclerotherapy for Arterio-Venous Malformation: A Case Report - Nair, Vipin; Sood, Chetan (Lietuvos chirurgija, 2025)
Introduction. Acquired arteriovenous malformations (AVMs) often result from minor trauma. AVMs exhibit diverse clinical manifestations and an unpredictable clinical course. This document addresses the management challenges associated with restoring mobility in a patient who experienced severe extension lock of the right knee following repeated sclerotherapy for an extensive arteriovenous malformation of the right vastus lateralis muscle. Main symptoms and important clinical findings. The patient sustained a contusion of the right thigh after a trivial trauma, subsequently developing an extensive arteriovenous malformation in the right vastus lateralis over several years. The patient underwent multiple sclerotherapy sessions with 10% polidocanol for AVM control over one year. Gradually, the patient’s right knee became locked in extension, resulting in functional disability. The main diagnoses, therapeutic interventions, and outcomes. Clinical examination revealed a 10x8 cm stony hard swelling in the lateral aspect of the right thigh. MRI indicated a low-flow venous malformation involving the right vastus lateralis with atrophy of the proximal portion. A CT-angiogram identified a feeder from the medial circumflex femoral artery. The patient underwent surgical exploration and excision of the sclerosed vastus lateralis and part of the vastus intermedius muscle, with a Tensor Fascia Lata graft applied to the exposed femoral bone surface. The patient recovered well, achieving an active knee flexion of 110 degrees, and is now able to sit and drive comfortably. Conclusion. The treatment of AVMs presents significant challenges. Minimally invasive methods are foundational to management but can lead to severe soft tissue fibrosis and functional disability. Surgery becomes necessary in complicated cases and for managing complications arising from minimally invasive procedures. Optimal outcomes require individualized multi-departmental management for all patients.